Inertia in plant community structure: state changes after cessation of nutrient-enrichment stress - Lauenroth, W. K., author; Milchunas, D. G., author; Ecological Society of America, publisher (Colorado State University. Libraries, 1995)
Water, nitrogen, and water-plus-nitrogen at levels beyond the range normally experienced by shortgrass steppe communities were applied from 1971 through 1975, plant populations were sampled through 1977, and the results of the experiment were published. Upon revisiting the plots in 1982, we found it apparent that large changes had occurred since 1977. Sampling was re-established in 1982 to follow trajectories of recovery. Our purposes in this paper are to examine how conclusions from this study changed through time, and discuss implications of these changes for monitoring potentially stressed ecosystems. Although productivities increased, dissimilarities in plant species composition at the end of the 5 year of nutrient treatments were not significantly different from controls. Two years after cessation of the treatments exotic "weed" species were increasing in water plus-nitrogen treated communities, and community dissimilarities were diverging in water and water-plus-nitrogen treated communities. Seven years after cessation of treatments all communities were significantly different from controls. Exotics were more than ten times more abundant in water-plus-nitrogen and nitrogen treated communities than they had been2 year post-treatment. A consistent trend in recovery of all treated communities was evident over the next 5 yr. However, the trend towards recovery reversed over the next four consecutive years in the previously water-plus-nitrogen and water treated communities. The four-to-five year cycles in species composition and abundance of exotics towards, and then away from, conditions in undisturbed control communities were not related to weather, but large accumulations of litter suggested biotic regulation. Inertia of existing plant populations, or the tendency to continue to occupy a site when conditions become unfavorable, can mask both future deterioration in ecosystem condition and unstable behavior resulting from environmental stressors. Time lags in initial response means that an ecosystem can pass a threshold leading to transitions to alternate states before it is evident in structural characteristics such as species composition. Global climate change and sulfur and nitrogen oxide pollutants also have the potential to act as enrichment-stressors with initial time lags and/or positive effects and cumulative, subsequent negative effects, rather than as disturbance forces with immediate negative impacts. Sociopolitical systems, however, often require change in biological variables or negative impacts before acting to ameliorate environmental problems. The manner in which conclusions changed at various periods in time, and the potential for time lags in responses of species populations, raises questions about which variables are most useful for detection of stress and how long studies must last to be useful.
Keywords: stability; semiarid grassland; population oscillations; nutrient enrichment; long-term monitoring; exotic weed invasions; disturbance; succession; time lags